Accountability of Tourist Police Bureau - Sinphibarl, Norranot; Somphong, Saruda (Dhammathas Academic Journal, 2019)
This research has the objectives: 1) Study the current state of the structure of tourist police bureau; 2) Study the responsibility of tourist police bureau; 3) propose the responsibility guidelines of tourist police bureau this research qualitative research the target group is 3 related persons: 1) the person responsible for the administration of tourist police bureau national police bureau 12 people; 2) tourist police 5 people; 3) 10 tourists, total of 27 people, then create an interview research tool to analyze data from in-depth interviews analyze various documents, analyze the results and explain the phenomenon.This research has the objectives: 1) Study the current state of the structure of tourist police bureau; 2) Study the responsibility of tourist police bureau; 3) propose the responsibility guidelines of tourist police bureau this research qualitative research the target group is 3 related persons: 1) the person responsible for the administration of tourist police bureau national police bureau 12 people; 2) tourist police 5 people; 3) 10 tourists, total of 27 people, then create an interview research tool to analyze data from in-depth interviews analyze various documents, analyze the results and explain the phenomenon. The results of the research found that: 1. The current condition of the structure of tourist police bureau has a structure of personnel structure budget structure, size of organization technology structure the structural process that needs to be improved is the decentralization of administrative services for tourists to have interpreters on a regular basis. legal treatment and security for tourists should develop information technology that will help facilitate various tourism the responsibility of tourist police bureau regarding the structure of tourist police bureau, it was found that most of them were knowledgeable, capable, able to perform their duties well. and have ethics that are appropriate to the position of duty. 2. The structure of the mission of the tourist police, including the security structure legal treatment and providing one stop service to provide convenience, friendly to tourists and the general public. 3. Security structure improve information and communication systems to be up to date. Legal structure strictly violating the illegal of foreign workers, smuggling into the city, controlling wrongdoing in the structure of human trafficking and punishing the perpetrators.